Using Augmented Reality Based LKPD to Improve Mathematics Learning - Rizkiana, Elis; Agustiani, Riza; Wardani, Ambarsari Kusuma (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2025)
This study develops a learning medium as a Student Worksheet (LKPD) based on Augmented Reality (AR) to support mathematics learning. The media is available only on Android devices and was developed using the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. Research instruments include interviews, evaluation tests, validation sheets, and student response surveys. Mathematical education lecturers conducted validation, while practicality testing consisted of individual, small-group, and field trials. Data were analyzed both quantitatively and subjectively. The validity results showed a score of 0.78 with the category “at the moment”. The practical result indicated that the AR-based LKPD was in the “highly practical” category, with an average score of 4.24 and a completion rate of 83%. Moreover, AR-based LKPD enhanced student engagement, reduced learning fatigue, and improved mathematics learning outcomes. These findings imply that the AR-based LKPD can serve as an innovative alternative in mathematics learning and hold potential for broader implementation to improve the quality of teaching and learning processes